PIWI-interacting RNAs in cancer: Biogenesis, function, and clinical significance - Yao, Jie; Xie, Mei; Ma, Xidong; Song, Jialin; Wang, Yuanyong; Xue, Xinying (Frontiers in Oncology, 2022)
PIWI-interacting RNAs (piRNAs) are a less-studied class of small non-coding RNAs with approximately 24-31 nucleotides in length. They express in germline and somatic cells and form complexes with PIWI proteins to exert regulatory effects. New studies show that piRNAs are aberrantly expressed in various cancers. In this review, we focus on those piRNAs that are associated with cancer hallmarks such as proliferation, invasion, and chemoresistance, and discuss their potential as biomarkers for cancer diagnosis and prognosis.